2021
DOI: 10.3389/fpls.2021.689875
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic, Phytotoxic, and Insecticidal Effects of Thymus proximus Serg. Essential Oil and Its Major Constituents

Abstract: The chemical profile of Thymus proximus essential oil (EO) and its allelopathic, phytotoxic, and insecticidal activity was evaluated. Carvacrol, p-cymene, and γ-terpinene were detected as the major components of the EO, representing 85.9% of the total oil. About 50 g fresh plant material of T. proximus in a 1.5-L air tight container completely inhibited the seed germination of Amaranthus retroflexus and Poa anuua. Meanwhile, the EO exhibited potent phytotoxic activity, which resulted in 100% germination failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 89 publications
1
14
0
Order By: Relevance
“…The composition of bioactive secondary metabolites synthesized by herbal medicines varies widely depending on the plant species [ 24 , 29 , 30 ]. Thymus is a traditional medicinal herb in the mint family ( Lamiaceae ) and is well known worldwide for its ability to synthesize high quantities of essential oils, which have been widely used in pharmaceutical and food applications [ 31 , 32 , 33 , 34 ]. Individually, beneficial endophytic actinobacteria living within various plant tissues of herbal medicines have the potential for the production of many secondary metabolites with application in agriculture and pharmaceutical industries [ 13 , 14 , 15 , 16 , 17 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of bioactive secondary metabolites synthesized by herbal medicines varies widely depending on the plant species [ 24 , 29 , 30 ]. Thymus is a traditional medicinal herb in the mint family ( Lamiaceae ) and is well known worldwide for its ability to synthesize high quantities of essential oils, which have been widely used in pharmaceutical and food applications [ 31 , 32 , 33 , 34 ]. Individually, beneficial endophytic actinobacteria living within various plant tissues of herbal medicines have the potential for the production of many secondary metabolites with application in agriculture and pharmaceutical industries [ 13 , 14 , 15 , 16 , 17 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thymus fontanesii inhibited seed germination of Avena fatua , Cyperus rotundus , Sinapis arvensis , Sonchus oleraceus , and Xanthium strumarium [ 171 ]. Thymus proximus suppressed the seed germination of Amaranthus retroflexus and Poa anuua [ 192 ]. Thymus algeriensis inhibited Medicago sativa and Triticum astivum seedling growth [ 193 ].…”
Section: Botanical Herbicidesmentioning
confidence: 99%
“…Thymus algeriensis inhibited Medicago sativa and Triticum astivum seedling growth [ 193 ]. Many other Thymus species also showed phytotoxic effects to further herbs [ 192 ], indicating that thyme essential oil, in general, has high herbicidal potential and can be used in a wide range of weeds. Thymol and carvacrol were shown to be more phytotoxic than glyphosate, referring to the root growth of Echinochloa crus-galli [ 191 ].…”
Section: Botanical Herbicidesmentioning
confidence: 99%
“…One such option is the use of botanical pesticides, which have exhibited some control of crop pests ( Opolot et al., 2006 ; Tembo et al., 2018 ; Ngegba et al., 2022 ). Essential oils from aromatic plants and their major constituents, were considered to be alternatives to conventional synthetic pesticides for controlling many pests, due to several advantages including rapid degradation, low residual, and versatile mechanism of action ( Czerniewicz et al., 2018 ; Mostafiz et al., 2020 ; Zhou et al., 2021 ). For example, it was reported that the essential oil of Hemizygia petiolata Ashby containing high levels (>70%) of the sesquiterpene ( E )-β-farnesene, significantly reduced the numbers of pea aphid ( Acyrthosiphon pisum ) in the field-plot experiment ( Bruce et al., 2005 ).…”
Section: Introductionmentioning
confidence: 99%